The isolation and synthesis of neodolastane diterpenoids. Issue 2 (4th November 2014) - Marković, Dean; Kolympadi, Maria; Deguin, Brigitte; Porée, François-Hugues; Turks, Māris
Abstract : This account summarises the progress in isolation, characterisation and synthesis of diterpenoids sharing a tricyclic neodolastane skeleton as well as their biogenetic origin and diverse biological activities. Abstract : Covering: 2000 to 2014 The neodolastane diterpenoids comprise a group of 44 compounds including guanacastepenes, heptemerones, plicatilisins, radianspenes, 2, 15-epoxy-5, 13-dihydroxyneodolast-3-en-14-one and sphaerostanol. These fungal and marine natural products are characterized by a tricyclic neodolastane skeleton that consists of fused five-, seven- and six-membered rings. Their reported antibiotic activities against antibiotic-resistant bacteria together with strong antifungal and anticancer activities and their novel structures render these compounds interesting synthetic targets. The aim of this account is to summarise the progress in the isolation, characterisation and synthesis of these diterpenoids as well as to review their biogenetic origins and diverse biological activities since their discovery in 2000.